Risk Factors and Outcomes for Pandemic H1N1 Influenza Compared with Seasonal Influenza in Hospitalized Children in China - Qingli Zhang; Wei Ji; Zhongqin Guo; Zhenjiang Bai; Noni E MacDonald (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To compare clinical features and outcomes of children hospitalized in China with pandemic (p)H1N1 between 2009 and 2010 versus seasonal influenza A between 2008 and 2009.